Chronic Exertional Compartment Syndrome in the Leg: Comparing Surgery to Conservative Therapy - Vogels, Sanne; Ritchie, Ewan D.; Hundscheid, Henricus PH; van Someren, Kim; Janssen, Loes; Hoencamp, Rigo; Scheltinga, Marc R (International Journal of Sports Medicine, 2020)
The aim of this nonrandomized cohort study was to compare the clinical effectiveness of an elective fasciotomy with conservative treatment for chronic exertional compartment syndrome of the leg. Patients diagnosed with chronic exertional compartment syndrome who opted for surgery (n=188) completed a preoperative questionnaire and a 12-month postoperative questionnaire. Patients who continued conservative treatments (n=23) served as controls. Gender, age, sports activity or affected compartments were comparable, but intensity of pain was higher in the surgical group (at rest: 2.5±0.1 vs. 2.0±0.2, during exercise: 4.2±0.1 vs. 3.8±0.2; both p<0.05). Following treatment, surgical patients demonstrated a larger drop in intensity levels of pain (surgery 1.6±0.1, conservative 0.9±0.2, p=0.01) and tightness (surgery 1.4±0.1, conservative 0.4±0.3, p=0.00) during exercise. Success (good or excellent treatment effect) was attained in 42% of the surgical group compared to only 17% in the conservatively treated group (p=0.02). However, previous activity level was achieved in a mere 26% in the surgical treatment group and 35% in the conservative treatment group (p=0.33). A fasciotomy for chronic exertional compartment syndrome in the leg results in significantly decreased levels of pain and tightness and better satisfaction compared to patients who continued a conservative treatment regimen.
Keywords: chronic exertional compartment syndrome; fasciotomy; lower extremity; conservative treatment; cohort study